Uma proposta de abordagem da matemática financeira e educação financeira no ensino médio - CERQUEIRA, Stenio Henrique do Nascimento (2020)
This work has the objective to offer high school math teachers a way to teach Financial Math in high school, personal and familiar financial education as well, taking advantage of the relation between these two topic. Firstly, we are going to do a study of numeric strings and finit induction principle, whom will be base for demonstration that will be presented. Then, we are going to study main topics of Financial Math that we consider importante for the high school. Lastly, the Financial education, where we quote some instruments used in Brazilian’s financial life and we put problem situations that have relation between Financial Math and event in our reality.